Altruisme Sebagai Benteng Pertahanan Keluarga Di Era 4.0 (Penafsiran Qs. Al-Hasyr Ayat 9 Perspektif Tafsir Al-Tanwir Wa Al-Tahrir Dan Al-Mizan Fi Al-Tafsir) - Fairuz Dianah; Mohammad Hadi Sucipto; Abdul Djalal; Mohammad Kurjum (IAIN Tulungagung, 2020)
Abstract This paper discusses altruism in QS. Al-Hasyr verse 9 in Tafsir al-Tanwir wa al-Tahrir and al-Mizan fi al-Tafsir represented by lafadz خصاصة. Altruism is very important to be studied moreover it is related to the problems of the family of the 4.0 era today which are rife with discrimination of women, divorce, and economic problems. Returning to the values of religious altruism is one solution to build a family defense that is sakinah mawaddah and warahmah. The purpose of this study is to understand the comparison of Tafsir al-Tanwir wa al-Tahrir and al-Mizan fi al-Tafsir to understanding altruism khasasah and their implications for family defense in the 4.0 era. To achieve the objectives, the method use id qualitative method with a semantic approach. Through this reading the results obtained in study are; fist; altruism is understood as a voluntary activity carried out by a person or group to help others without expecting anything in return. Second; khasasahin QS. Al-Hasyr verse 9 has several meanings namely; 1) loving his brother because of God, 2) generous and far from being miserly, 3) putting this brother ahead of himself. Through this understanding, the implications derived from the substance of this study are the creation of altruism as a stronghold in the family in this era. Keywords: altruism, QS. Al-Hasyr: 9, Tafsir al-Tanwir wa al-Tanwir, al-Mizan fi al-Tafsir. Abstrak Tulisan ini membahas tentang altruisme dalam QS. Al-Hasyr ayat 9 pada Tafsir al-Tanwir wa al-Tahrir dan al-Mizan fi al-Tafsir yang direpresentasikan oleh lafadz خصاصة. Altruisme sangat penting dikaji apalagi dikaitkan dengan problem keluarga era 4.0 dewasa ini yang marak dengan diskriminasi perempuan, perceraiaan dan problem ekonomi. Mengembalikan pada nilai-nilai altruisme agama menjadi salah satu solusi untuk membangun pertahanan keluarga yang sakinah, mawaddah dan warahmah. Tujuan penelitian ini adalah untuk memahami komparasi Tafsir al-Tanwir wa al-Tahrir dan al-Mizan fi al-Tafsir terhadap pemahaman altruisme khasasahdan implikasinya terhadap pertahanan keluarga di era 4.0. Untuk mencapai tujuan tersebut, metode yang digunakan adalah metode kualitatif dengan pendekatan semantik. Melalui pembacaai ini, hasil yang diperoleh dalam penelitian ini adalah; pertama; altruisme dipahami sebagai kegiatan suka rela yang dilakukan seseorang atau kelompok untuk menolong orang lain tanpa mengharapkan imbalan apapun. Kedua; lafad khasasah dalam QS. Al-Hasyr ayat 9 memiliki beberapa makna yaitu; 1) mencintai saudaranya karena Allah, 2) dermawan dan jauh dari sifat kikir, 3) mengutamakan saudaranya daripada dirinya sendiri. Melalui pemahaman ini, implikasi yang didapat dari substansi penelitian ini adalah terciptanya altruisme sebagai benteng pertahanan dalam keluarga di era sekarang ini. Kata Kunci: altruisme, QS. Al-Hasyr: 9, Tafsir al-Tanwir wa al-Tahrir, al-Mizan fi al-Tafsir.